Use of otolith microchemistry as habitat indicator of Anchoa tricolor (Spix & Agassiz, 1829) in a subtropical estuary - de Carvalho, Barbara Maichak (2017)
The objective of the present study was to evaluate the use of sagitta otolith microchemistry (Sr:Ca, Ba:Ca ratios) as habitat indicator of Anchoa tricolor between the estuary and the adjacent continental shelf. We analyzed 162 specimens of A. tricolor in the Paranaguá Estuarine Complex (Brazil), and salinity and rainfall data. The biological and environmental data were grouped into sectors (internal, intermediate, and external) and periods (early and late wet, and dry periods). The concentrations of Ca, Ba and Sr were determined using an ICP-OES. The Sr:Ca ratio indicated the existence of two groups, probably from different origins, that use the estuary at the same time, but occupying different sectors of the estuary. The Ba:Ca ratio did not differentiate the groups as to the use of estuary, but rather revealed low values, suggesting that this species does not use freshwater environments. However, this ratio showed a high variation in the wet period, indicating a greater availability of barium in the estuarine regions affected by the river discharge. Considering our results, it is possible to classify A. tricolor as an estuarine migrant species. Also, the Sr:Ca and Ba:Ca ratios can be indicative of the habitat use in a subtropical estuary.